2003
DOI: 10.1097/00126334-200308010-00009
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Adherence to Highly Active Antiretroviral Therapy Over Time Among Clients Enrolled in the Treatment Adherence Demonstration Project

Abstract: Adherence to antiretroviral medications is essential to therapeutic success. Many published studies have investigated the degree of adherence or nonadherence, but sample sizes have generally been small, and adherence has seldom been viewed as a longitudinal process. This paper investigates the stability of adherence over time among HIV-infected individuals attending adherence support programs in New York State. The study cohort consists of 435 clients who were on HAART at baseline and who completed at least 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 48 publications
3
43
0
2
Order By: Relevance
“…However, it has been demonstrated that patients on HAART must take at least 95% of their medication doses consistently to lower their viral load count to less than 50 and to avoid developing drug resistance, [1][2][3] causing medication regimen adherence to be extremely difficult. Adherence to medication has been defined as having in place Division of Adolescent Medicine, Childrens Hospital Los Angeles, Los Angeles, California.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been demonstrated that patients on HAART must take at least 95% of their medication doses consistently to lower their viral load count to less than 50 and to avoid developing drug resistance, [1][2][3] causing medication regimen adherence to be extremely difficult. Adherence to medication has been defined as having in place Division of Adolescent Medicine, Childrens Hospital Los Angeles, Los Angeles, California.…”
Section: Introductionmentioning
confidence: 99%
“…2 Common barriers to HAART adherence have been described as complex dosing, debilitating side effects, depression, unstable housing, and limited social support. 3 With the development and increased use of twice-daily, or once-daily dosing for HAART therapy, the barrier of complex dosing schedules has been reduced. Longterm medication regimen adherence is challenging in all populations, but in the HIV infected adolescent population developmental factors (i.e., invulnerability, experimentation, etc.)…”
mentioning
confidence: 99%
“…4 Unfortunately, despite the importance of strict compliance, it is estimated that 18 to 54% of HIV-positive individuals are nonadherent to ART. 5,6 Estimation of patients´ adherence in studies included different methods. Besides electronic monitoring, pill counts and refill history which are complex, time consuming and impractical for most clinical settings, self-reported adherence although an indirect measure is simple and predicts important virological and immunological outcomes.…”
mentioning
confidence: 99%
“…U.S. studies have reported that as few as 18% to 73% of participants were non-adherent to antiretroviral therapy Tesoriero et al, 2003). These percentages may be even lower for PLWHs dealing with neurocognitive impairment, substance abuse problems, and added environmental and psychosocial constraints.…”
Section: Control and Prevention (Cdc) National Institutes For Healthmentioning
confidence: 99%
“…As much as 95% adherence may be necessary to achieve positive clinical outcomes. However, achieving the level of adherence necessary to suppress viral replication can be challenging, with recent studies reporting that anywhere between 18% and 73% of PLWH are non-adherent to antiretroviral therapy Tesoriero et al, 2003).…”
Section: Chapter V Transition To Manuscriptmentioning
confidence: 99%